To determine which system has (4, -3) as a solution, we can plug the values \(x = 4\) and \(y = -3\) into each equation in the systems provided.
System 1:
-
\(7x + 9y = 55\)
- Substitute \(x = 4\) and \(y = -3\): \[ 7(4) + 9(-3) = 28 - 27 = 1 \quad (\text{not } 55) \]
-
\(3x + 9y = -15\)
- Substitute \(x = 4\) and \(y = -3\): \[ 3(4) + 9(-3) = 12 - 27 = -15 \quad (\text{true}) \]
System 2:
-
\(7x - 9y = 55\)
- Substitute \(x = 4\) and \(y = -3\): \[ 7(4) - 9(-3) = 28 + 27 = 55 \quad (\text{true}) \]
-
\(3x - 9y = -15\)
- Substitute \(x = 4\) and \(y = -3\): \[ 3(4) - 9(-3) = 12 + 27 = 39 \quad (\text{not } -15) \]
System 3:
-
\(7x + 9y = 55\)
- Substitute \(x = 4\) and \(y = -3\): \[ 7(4) + 9(-3) = 28 - 27 = 1 \quad (\text{not } 55) \]
-
\(3x - 9y = -15\)
- Substitute \(x = 4\) and \(y = -3\): \[ 3(4) - 9(-3) = 12 + 27 = 39 \quad (\text{not } -15) \]
System 4:
-
\(7x - 9y = 55\)
- Substitute \(x = 4\) and \(y = -3\): \[ 7(4) - 9(-3) = 28 + 27 = 55 \quad (\text{true}) \]
-
\(3x + 9y = -15\)
- Substitute \(x = 4\) and \(y = -3\): \[ 3(4) + 9(-3) = 12 - 27 = -15 \quad (\text{true}) \]
Conclusion:
(4, -3) is the correct solution to System 4: \[ 7x - 9y = 55 \] \[ 3x + 9y = -15 \]